Reinforced ultra-high performance concrete beam under flexure and shear: Experiment and theoretical model - Ziwei Cai; Xinzhi Duan; Lingfei Liu; Zhoudao Lu; Junhong Ye (Case Studies in Construction Materials, 2024)
This paper investigated the influence of different shear span ratios, longitudinal (LR) and stirrup (SR) reinforcement ratios, and material types on the flexural and shear performance of reinforced ultra-high performance concrete (UHPC) beams. A series of bending tests with shear span ratios of 4.0, 1.5, and 1.0 were conducted. Results reveal that UHPC beams with a LR ratio of 2.53% exhibit 1.66, 2.00, and 1.45 times higher load capacity than that of the beams with a LR ratio of 1.34% at shear span ratios of 4.0, 1.5, and 1.0, respectively. A SR ratio of 1.40% can achieve 15% and 35% enhancement in load capacity of UHPC beams at shear span ratios of 1.5 and 1.0, respectively. The UHPC beams made with hybrid polyethylene and straight steel fibers have the highest load capacity compared to the beams with straight steel fibers and hooked steel fibers. The enhancement can achieve 8%, 5%, and 15% at shear span ratios of 4.0, 1.5, and 1.0, respectively. Furthermore, cross-section analysis, a novel truss-arch model, and strut-and-tie model were employed to theoretically calculate the load capacity of the UHPC beams with different failure modes. The relative errors of the cross-section analysis and truss-arch model are smaller than 9% and 25%. The findings of this work could provide guidelines for the structural design of UHPC beams under different loading conditions.